Development of Animated Video Media About Students' Learning Interests at MTsT Daarut Tahfizh Al-Ikhlas - Imam Hamdani; Yuliana Nelisma; Tengku Febri Irwansyah (International journal of technology and education research, 2025)
This study aims to develop animated video media that can increase students' interest in learning at MTsT Daarut Tahfizh Al-Ikhlas and to determine the effectiveness of its use in improving students' understanding of learning materials. Based on the formulation of the problem proposed, this study focuses on two main aspects, namely the development of animated video media and its effectiveness in increasing students' interest and understanding. This study uses a research and development approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, questionnaires, and tests to measure students' interest in learning and understanding before and after using video media. The results of the study indicate that the developed animated video media can attract students' attention and increase their interest in learning. In addition, the use of animated video media has proven effective in helping students understand learning materials better. Based on these findings, it is suggested that animated video media can be implemented more widely in the learning process to improve the quality of education and student learning outcomes.